2015
DOI: 10.1039/c4cy00998c
|View full text |Cite
|
Sign up to set email alerts
|

TiO2-supported heteropoly acid catalysts for dehydration of methanol to dimethyl ether: relevance of dispersion and support interaction

Abstract: Two heteropoly acids (HPAs) with Keggin structures, namely, H 3 PW 12 O 40 (HPW) and H 4 SiW 12 O 40 (HSiW), have been deposited on TiO 2 and used as catalysts for the production of dimethyl ether (DME) from methanol. The catalysts have been prepared by incipient wetness impregnation of HPW and HSiW on TiO 2 with HPA loadings ranging between 0.9 and 9.0 Keggin units (KU) per square nanometer. The structure and acid properties of the final catalysts have been thoroughly characterized by N 2 adsorption-desorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 60 publications
5
76
0
Order By: Relevance
“…Development of new and cheap catalysts for MTD process on a large scale is of great interest. Usually, methanol is converted over solid catalyst either as simply dehydration, yielding DME and water, or as deep dehydration, producing hydrocarbons [22]. At the reaction conditions used [240-300 °C]; hydrocarbons products were hardly detected as a side reaction product [10].…”
Section: Effect Of Catalyst Weightmentioning
confidence: 99%
“…Development of new and cheap catalysts for MTD process on a large scale is of great interest. Usually, methanol is converted over solid catalyst either as simply dehydration, yielding DME and water, or as deep dehydration, producing hydrocarbons [22]. At the reaction conditions used [240-300 °C]; hydrocarbons products were hardly detected as a side reaction product [10].…”
Section: Effect Of Catalyst Weightmentioning
confidence: 99%
“…The catalytic hydrogenation of CO 2 to methanol is considered one of the most promising processes because methanol can be used as an energy carrier for fuel cell application [1][2][3]. Moreover, methanol can be converted to dimethyl ether (DME) [4,5] which is considered as a feasible fuel for diesel engines [6,7], or into higher hydrocarbons according to methanol-to-olefins (MTO) process [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Since HPW is soluble in water and many organic solvents, it must be first immobilized on an insoluble support, such as SiO 2 , titanium dioxide (TiO 2 ), zeolite and/or active carbon, in order to make heterogeneous HPW catalysts . Some studies have shown that supported HPW catalysts might have similar or even higher activities, compared to bulk HPW, for catalyzing dehydration reactions . The slightly increased activities might be attributed to the adsorption of reactants on the supports, leading to the increased local reactant concentrations near HPW active sites .…”
Section: Introductionmentioning
confidence: 99%